2016
DOI: 10.3329/cmoshmcj.v15i1.28756
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Smoking Among Tuberculosis Patients : An Analysis in A Tertiary Care Hospital

Abstract: Background: Tuberculosis is among the major causes of illness and death worldwide especially in Asia. Smoking is associated with recurrent tuberculosis and its related mortality. Also, it could affect clinical manifestations, bacteriological conversion and outcome of treatment. This study aimed to evaluate the pattern of tobacco smoking, history of previous quit attempts and attitude towards quitting in tuberculosis patients. Materials and Methods: It was a cross-sectional study done amongst tuberculosis patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…This finding was similar to those of previous studies from India, Ethiopia, and China, which have reported that most people understand that tuberculosis can spread to others, but they lack the knowledge about the basic tuberculosis prevention measures [[39], [40], [41]]. This lack of knowledge contributes to the feelings of fear regarding tuberculosis transmission to other family members, particularly to children, and anxiety about their children's future [19,42].…”
Section: Discussionsupporting
confidence: 88%
“…This finding was similar to those of previous studies from India, Ethiopia, and China, which have reported that most people understand that tuberculosis can spread to others, but they lack the knowledge about the basic tuberculosis prevention measures [[39], [40], [41]]. This lack of knowledge contributes to the feelings of fear regarding tuberculosis transmission to other family members, particularly to children, and anxiety about their children's future [19,42].…”
Section: Discussionsupporting
confidence: 88%
“…The 48.5% prevalence of any mental illness is higher compared to findings of a study in Pakistan with a rate of 31%, Nigeria at 32% and a pooled rate of 34% in a meta-analysis [ 19 , 33 , 34 ]. It is however lower than 82% rate in South Africa [ 35 ].…”
Section: Discussionmentioning
confidence: 54%
“…They reported that depressive illness was the commonest (39.83%, n= 43) and others were anxiety (30.5%), somatoform (10.1%), psychotic spectrum disorder (8.3%), personality disorder (6.4%) and substance use disorder (3.1%). 25 The prevalence of depression in TB patients obtained in the present study is on the higher side and only depression parameter is analysed. Moussavi et al analysed data concerning people older than 18 years and reported the prevalence of depression in the whole sample was 3.2%, but it reached 9.3% among those who reported diabetes, 10.7% among those who had arthritis and 18.1% among asthmatic individuals.…”
Section: Resultsmentioning
confidence: 99%